The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0223337
|View full text |Cite
|
Sign up to set email alerts
|

A tailored approach to fusion transcript identification increases diagnosis of rare inherited disease

Abstract: BackgroundRNA sequencing has been proposed as a means of increasing diagnostic rates in studies of undiagnosed rare inherited disease. Recent studies have reported diagnostic improvements in the range of 7.5–35% by profiling splicing, gene expression quantification and allele specific expression. To-date however, no study has systematically assessed the presence of gene-fusion transcripts in cases of germline disease. Fusion transcripts are routinely identified in cancer studies and are increasingly recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 58 publications
(67 reference statements)
0
30
0
Order By: Relevance
“…Thus, detection algorithms primarily trained with oncogenic fusions may be biased by these and not optimized to account for different expression levels and patterns of read support. Such difficulties were demonstrated in our study where TopHat Fusion (Kim and Salzberg, 2011) using default parameters succeeded in detecting only one of eight fusion events detected and laboratory-validated in our rare disease cohort (Oliver et al, 2019b). To address this, we implemented a series of filtering and classification steps to detect fusions potentially linked to rare genetic constitutive disease.…”
Section: Adapting Fusion Detection To Rare Diseasementioning
confidence: 94%
See 4 more Smart Citations
“…Thus, detection algorithms primarily trained with oncogenic fusions may be biased by these and not optimized to account for different expression levels and patterns of read support. Such difficulties were demonstrated in our study where TopHat Fusion (Kim and Salzberg, 2011) using default parameters succeeded in detecting only one of eight fusion events detected and laboratory-validated in our rare disease cohort (Oliver et al, 2019b). To address this, we implemented a series of filtering and classification steps to detect fusions potentially linked to rare genetic constitutive disease.…”
Section: Adapting Fusion Detection To Rare Diseasementioning
confidence: 94%
“…Discussion of fusion transcripts detected in normal tissues centered on apparently benign events resulting from co-transcription of neighboring genes or more controversially from trans-splicing (Akiva et al, 2006;Peng et al, 2015;Babiceanu et al, 2016;Yuan et al, 2017;He et al, 2018). Reports of fusions in the context of inherited disease existed only in isolated case studies and were not systematically reported on until 2019 (Oliver et al, 2019b). The formulation of computational fusion detection software reflected the field's focus on oncology-related fusion events and algorithms were primarily trained using incompletely characterized tumors or cancer cell-lines (Kumar et al, 2016).…”
Section: Adapting Fusion Detection To Rare Diseasementioning
confidence: 99%
See 3 more Smart Citations